Spectral Diagnosis of Atmospheric Pressure Plasma Jet - Pang1, Jia-Yu; Tang1, Xiao-Liang; Shao1, Ming; Wen1, Dan; Qiu1, Gao (Asian Journal of Chemistry, 2014)
A self-made atmospheric pressure plasma jet reactor on intermediate frequency is presented in this paper. The working gas argon went through the quartz tube and the plasma was generated from a nozzle at atmospheric pressure. The active species generated in the plasma were investigated by optical emission spectroscopy. Through the analysis of the emission spectrum in a series of experiments, it is confirmed the existence of some free radicals, by analysis of the relative strength of active species and the possible dissociation process. There exist large differences in the activity species of plasma between in air environment and in the quartz tube and nitrogen is the most important factor. The experimental results indicate that spectral diagnosis has been proved a workable method and optical emission spectroscopy diagnosis is significant for the research of chemical principle in plasma. Thus, it is important to the application in plasma polymerization and material modification.